2010
DOI: 10.1111/j.1399-3046.2009.01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric liver transplantation for primary malignant liver tumors with a focus on hepatic epithelioid hemangioendothelioma: The UNOS experience

Abstract: Treatment for HEH does not follow a standardized algorithm. From clinical experience, it is assumed that pediatric patients with HEH will fare as well as other common pediatric liver tumors post-OLT. The UNOS dataset was examined for patients with pediatric OLT between 1987 and 2007. Patients were grouped into non-tumors, HB, HCC, HEH, and rare liver tumors. COD analysis was calculated using Fisher's exact test. Patient, allograft, and recurrence-free survival were compared using Kaplan-Meier curves and log-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…The widespread application of OLT for children diagnosed with hepatic malignancies has been well established. In a recent review of the United Network for Organ Sharing database, 366 children were identified who underwent OLT for the indication of liver neoplasm between 1987 and 2007 . The most common indication was hepatoblastoma, which was followed by hepatocellular carcinoma and hepatic epithelioid hemangioendothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread application of OLT for children diagnosed with hepatic malignancies has been well established. In a recent review of the United Network for Organ Sharing database, 366 children were identified who underwent OLT for the indication of liver neoplasm between 1987 and 2007 . The most common indication was hepatoblastoma, which was followed by hepatocellular carcinoma and hepatic epithelioid hemangioendothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation has been proposed as the treatment of choice for those with unresectable liver disease (5‐year overall survival rates ranging from 55 to 83%) . However, recurrent allograft disease was observed in 24–33% of patients, and survival postliver transplant appears to be relatively unfavorable for children with EHE . In our series, one of four children transplanted died from transplant complications.…”
Section: Discussionmentioning
confidence: 68%
“…Zenge et al opined that resection be reserved for patients with life-threatening complications or suspected malignant tumours,8 while Samuel and Spitz recommended primary resection in all patients with symptoms with readily resectable solitary tumours 9. Though liver transplantation has also been recommended as a life saving option for severely patients with symptoms with multifocal IHE, new data suggest that 5-year survival (60.6%) may not be as high as previously believed10 and whenever possible, alternative treatment options should be considered 11. Steroids and IFN form the backbone of pharmacologic therapy.…”
Section: Discussionmentioning
confidence: 99%